Political-electoral dynamics in zones of paramilitary influence: analysis of competition and electoral participation (2009)
Some general considerations on the association between paramilitarism and politics and on the challenges for democracy, arising from the interference of armed actors in electoral processes, are presented in the first part of the article. The second part focuses on the description of electoral participation and competition and their main variations in municipalities of the Atlantic Coast in the last decades. The third part discusses the relationship between the changes in the variables under consideration and the presence of paramilitary groups in the municipalities of the four departments comprising the region of study. The fourth part examines the effects of armed actors’ presence and, particularly, of paramilitary groups, on electoral participation and competition, by means of a regression model.